Limb saving with regenerative medicine tactics - a case report - Contoli Isoldi, F; Vieites, L; Reis, A K De Sá; Ferreira, L M (Acta chirurgiae plasticae, 2025)
Regenerative medicine has gained significant attention due to its diverse strategies for tissue restoration and restructuring. This therapeutic approach combines knowledge from cellular biology, tissue engineering, and translational medicine, providing new hope for treating conditions that previously lacked definitive therapeutic options. Although natural tissue regeneration occurs in some organs, such as the liver, and in superficial epidermal injuries, this process is limited. Tissue regeneration involves replacing damaged cells with cells of the same type, fully restoring tissue structure and function, while healing often results in scar tissue that may not have the same functional properties. Given this limitation, regenerative medicine aims to enhance the body's regenerative capacity. The manipulation of growth factors, such as platelet-derived growth factor and vascular endothelial growth factor, has been shown to increase vascularization and cell proliferation. Autologous fat grafting has emerged as a vital tool in regenerative medicine, demonstrating efficacy in promoting tissue regeneration due to its rich composition of mesenchymal stem cells and growth factors. Case studies illustrate that lipografting can improve wound healing in patients with chronic ulcers and contribute to aesthetic and functional outcomes in breast reconstruction. This study reports a case of a 27-year-old male who sustained severe trauma to his left hand in a car accident, resulting in complex injuries. Despite the potential for amputation, the decision was made to preserve the limb. A series of surgical interventions, including necrotic tissue debridement and lipografting, were conducted over several weeks, resulting in significant tissue regeneration. By the fifth week, the wound bed exhibited adequate granulation tissue, and a skin graft was applied, demonstrating successful integration and functional recovery. This case underscores the potential of regenerative medicine techniques, specifically lipografting, in limb salvage and tissue repair. Further research is needed to enhance understanding and application of these strategies in treating complex wounds and improving patient outcomes.
Keywords: limb salvage; tuková tkáň; regenerativní lékařství; Regenerative Medicine; Limb Salvage; Adult; Male; Wound healing; dospělí; lidé; mužské pohlaví; Wound Healing; Adipose Tissue; fat grafting; regenerative medicine; Humans; záchrana končetiny; hojení ran